(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores modern approaches to enhancing digital literacy among students in higher education. As digital technologies rapidly evolve, universities must equip learners with advanced skills such as information evaluation, digital communication, cybersecurity awareness, and problem-solving through technology. The article examines key strategies including the integration of digital tools into teaching, development of information and media literacy, the use of collaborative platforms, promotion of data-driven problem-solving, and improvement of cybersecurity knowledge. It also highlights the importance of professional development for instructors and expanding access to digital infrastructure. These innovative approaches collectively contribute to preparing students for academic success and future professional environments.